Tingkat Kebugaran Jasmani Ekstrakurikuler Pencak Silat Pada Masa Covid-19 SMAN 1 Kabandungan - Abidin, Jaenal -; Gani, Ruslan Abdul; Purnamaningsih, Ine Rahayu (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
Physical fitness is a person's ability to carry out activities in the form of work in a relatively long period of time efficiently, which is carried out all day long without feeling tired which means that they still have more energy to enjoy free time after doing activities. During the Covid-19 period, there were restrictions on daily activities, especially movement activities, with a lack of movement activity that could affect the level of physical fitness, therefore, this study aims to determine the level of physical fitness of students who take part in extracurricular pencak silat during the Covid-19 period at SMAN 1 Kabandungan. This research is a quantitative descriptive study with a survey approach. The subjects in this study were all students who took part in extracurricular pencak silat at SMAN 1 Kabandungan totaling 20 people. The data analysis technique uses descriptive quantitative analysis with percentages and is assisted by the Microsoft Excel application. Based on the results of research and discussion, it was obtained that the average value of the physical fitness level of students who took part in extracurricular pencak silat during the Covid-19 period was 302.45 which was in the 251-310 interval, from consideration of the average value obtained, it was concluded that the level of physical fitness students who take extracurricular pencak silat are in the less category.